2004
DOI: 10.1038/sj.sc.3101667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abdominal binding on breathing patterns during breathing exercises in persons with tetraplegia

Abstract: Study design: Cross-sectional, experimental. Objectives: To investigate and compare static lung volumes and breathing patterns in persons with a cervical spinal cord lesion during breathing at rest, ordinary deep breathing, positive expiratory pressure (PEP) and inspiratory resistance-positive expiratory pressure (IR-PEP) with and without an abdominal binder (AB). Setting: The outpatient clinic at the Spinal Unit at Sahlgrenska University Hospital, Go¨teborg, Sweden. Method: The study group consisted of 20 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 17 publications
3
24
0
2
Order By: Relevance
“…As in other studies, [9][10][11]13 there were no reports of discomfort and no side-effects were observed, indicating that the use of abdominal binders is safe, simple, inexpensive and well tolerated by patients.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…As in other studies, [9][10][11]13 there were no reports of discomfort and no side-effects were observed, indicating that the use of abdominal binders is safe, simple, inexpensive and well tolerated by patients.…”
Section: Discussionsupporting
confidence: 79%
“…It also pushes the abdominal contents inward, moving the diaphragm upward and increasing its length during coughing, allowing the diaphragm to contract more effectively 21 and the subject to generate higher intrathoracic pressure during forced expiration. 13 In addition, the increased pressure over the abdomen would increase the fulcrum effect of the abdominal contents on the diaphragm and increase its efficiency. This would lead to an increase in inspiratory volume before coughing, thereby increasing the PEFR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Abdominal binders (ABs) have been used to aid respiratory function in people who have suffered SCI. [3][4][5][6][7][8][9][10][11][12][13] Several studies have reported that vital capacity (VC) in tetraplegic SCI is decreased to 50-80% of predicted values. 14,15 The mechanism of action of ABs is thought to be related to improving respiratory mechanics.…”
Section: Introductionmentioning
confidence: 99%